OPTIMIZATION OF THE DEBT OF A CRITICAL INFRASTRUCTURE ENTERPRISE IN TERMS OF STRENGTHENING FINANCIAL AND ECONOMIC SECURITY - HLUSHKO, Alina; PYRIH, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the issues of strengthening the financial and economic security of critical infrastructure enterprises of Ukraine under martial law. It is proved that the optimality of the volumes of receivables and payables, their balance, and timeliness of repayment are the basis for ensuring liquidity, solvency, financial independence, and safe functioning of the business entity as a whole. The article analyzes the dynamics, structure, ratio and indicators of turnover of accounts receivable and accounts payable of the critical infrastructure object of JSC "POLTAVAOBLENERGO". The influence of accounts receivable on the liquidity of the enterprise, its profitability and financial stability is determined. The influence of accounts payable on the financial independence of an enterprise and its solvency is substantiated. The indirect impact of accounts payable on the profitability of an enterprise is proved. It is established that the uncertainty and variability of the business environment, especially under martial law, complicates the process of making management decisions. The level of their validity and effectiveness depends on the ability of management to foresee possible scenarios. Therefore, forecasting is rightly recognized as an integral part of determining the directions of debt optimization. On the basis of forecasting, the risk of debt growth of the researched enterprise is identified and directions for optimizing the amount of receivables and payables are proposed, which will not only improve financial stability but also strengthen the financial and economic security of the enterprise as a whole. The priority measures to optimize the accounts payable of JSC "POLTAVAOBLENERGO" are as follows: introduction of a system of control over accounts receivable and accounts payable at the enterprise; introduction of control over the quality of services provided to consumers; monitoring of settlements with creditors for deferred or overdue debts and identifying reasons for non-compliance with the terms of the contract; obtaining state support under martial law.